2014
DOI: 10.1084/jem.20140283
|View full text |Cite
|
Sign up to set email alerts
|

Hrd1-mediated BLIMP-1 ubiquitination promotes dendritic cell MHCII expression for CD4 T cell priming during inflammation

Abstract: Yang et al. demonstrate that Hrd1 plays an important role in DC induction of CD4 T cell immunity. The underlying mechanism involves the ability of Hrd1 to ubiquitinate and degrade BLIMP-1, thus releasing CIITA from transcriptional repression and promoting MHCII expression. As a consequence, Hrd1−/− DCs protect mice from MOG-induced experimental autoimmune encephalomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 58 publications
3
77
0
Order By: Relevance
“…Recently, Blimp-1 was shown to be ubiquitinated by a ubiquitin ligase, Hrd1, in dendritic cells. 31 The precise ubiquitination sites on Blimp-1 and whether Hrd1 is also involved in Blimp-1 ubiquitination and degradation in MM cells await further studies. Although we here show that downregulation of Aiolos and Ikaros by CUL4A is important for the anti-MM effects of lenalidomide, we could not exclude the possibility that other targets of CUL4 may also have a role in this context.…”
Section: 13mentioning
confidence: 99%
“…Recently, Blimp-1 was shown to be ubiquitinated by a ubiquitin ligase, Hrd1, in dendritic cells. 31 The precise ubiquitination sites on Blimp-1 and whether Hrd1 is also involved in Blimp-1 ubiquitination and degradation in MM cells await further studies. Although we here show that downregulation of Aiolos and Ikaros by CUL4A is important for the anti-MM effects of lenalidomide, we could not exclude the possibility that other targets of CUL4 may also have a role in this context.…”
Section: 13mentioning
confidence: 99%
“…During ERAD, misfolded proteins within the ER bind to chaperones such as BiP and are retrotranslocated into the cytosol to be ubiquitinated by the cytosolic RING (really interesting new gene) domain of Hrd1 (19). Whereas Hrd1 is required for the clearance of misfolded proteins during ERAD, emerging evidence suggests that Hrd1 can also regulate cellular functions by controlling the availability of specific proteins, such as Nrf2, Blimp1, and PGC-1β (21)(22)(23). In this paper, we report that Hrd1 plays a crucial role at the B-cell survival checkpoint by degrading the death receptor Fas during peripheral B-cell activation to downmodulate AICD.…”
mentioning
confidence: 99%
“…We found that miR-125b was lower in B cells from CD40 teasomal inhibitor MG132, indicating that CD40 signaling may engage this pathway to control BLIMP-1 at the protein level. It has been shown recently that BLIMP-1 in dendritic cells is targeted for ubiquitination and proteasomal degradation by the ERresident protein HRD1, leading to enhanced MHC-II expression and T cell priming (18). HRD1 is also involved in the ubiquitination and degradation of misfolded proteins, unassembled secretory IgM H chains (20,(26)(27)(28), and IRE-1a, which is induced when unfolded proteins accumulate after sustained ER stress that accompanies the classical UPR in PCs, where it splices XBP-1, which has several downstream functions in secreting cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…5D). Further, when WT B cells were treated with the proteasomal inhibitor MG132, IRE-1a and BLIMP-1 amounts increased (Fig 5E), indicating that targeting of these proteins for proteasomal degradation via HRD1-mediated ubiquitination was involved (18,20). Thus, constitutive CD40 signaling in naive B cells reduces cellular Blimp-1 amounts by targeting both transcript and protein via independent pathways.…”
Section: Cd40 Ligation Induces Hrd1 That Targets Blimp-1 and Ire-1a Pmentioning
confidence: 93%
See 1 more Smart Citation